VOCATIONAL HIGH SCHOOL STUDENTS' PERCEPTION ON THE USE OF TASK-BASED LEARNING (TBL) IN SPEAKING CLASS - Isnavira, Silvanda; Sujannah, Wahyu Diny (E-Link Journal, 2023)
Task-based learning (TBL) has been widely discussed among recent researchers. Its implementation is proven to be beneficial for English as foreign language teaching method. Many previous studies bring in its evident efficacy to increase vocational high school students' basic language abilities. This study used survey research that aimed to explore vocational high school students' perception on the use of TBL to enhance their speaking skills. Quantitative data were obtained through a questionnaire as the instrument which was distributed to approximately 103 11th grade Office Authorization and Governance students at one of vocational high schools in Kediri. The findings revealed that students had a positive perception on the use of TBL to enhance their speaking skills because they felt relaxed when they are taught English using TBL, they feel motivated to learn English using TBL, and they perceive that TBL should be used more during English class. Furthermore, they also saw improvements in their speaking skills, in terms of fluency, pronunciation, grammar, and vocabulary. This study was to gain perceptions on task-based activities limited to discussions, presentations, and giving and receiving feedback and it was focused on learning descriptive text. A suggestion for the teachers is they may broaden the variation of the task-based activities while teaching the students, thus it could adapt to different genre texts. The researchers also came up with a recommendation for future researchers to explore students' perceptions of their difficulties when the teachers implement TBL. Keywords: task-based learning, speaking skills, English for Specific Purposes